2015
DOI: 10.1093/jrr/rrv073
|View full text |Cite
|
Sign up to set email alerts
|

External effective radiation dose to workers in the restricted area of the Fukushima Daiichi Nuclear Power Plant during the third year after the Great East Japan Earthquake

Abstract: Since the Great East Japan Earthquake on 11 March 2011, Iitate Village has continued to be classified as a deliberate evacuation area, in which residents are estimated to receive an annual additional effective radiation dose of >20 mSv. Some companies still operate in Iitate Village, with a special permit from the Cabinet Office Team in Charge of Assisting the Lives of Disaster Victims. In this study, we measured the annual effective radiation dose to workers in Iitate Village from 15 January to 13 December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In addition, it might be possible that the public who were particularly concerned about radiation tended to respond to the questionnaire of this survey, which could affect the statistics in an unexpected way. Further study with sufficient improvement on the points above is undertaken by our group in an ongoing way [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it might be possible that the public who were particularly concerned about radiation tended to respond to the questionnaire of this survey, which could affect the statistics in an unexpected way. Further study with sufficient improvement on the points above is undertaken by our group in an ongoing way [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, employees who wished to continue working in the factory were allowed to work 5 days a week and 10 hours a day. Due to the evacuation order, they were not allowed to live in the village of Iitate and they had to commute from their temporary houses located outside the village, sometimes with travelling time of more than one hour (Public Information Journal of Iitate, 2012;Sakumi et al, 2016).…”
Section: Case Studymentioning
confidence: 99%
“…The results showed that for this period the annual external effective dose including natural background was less than 2 mSv for 70% of the workers. The maximum annual effective dose reached 3.6 mSv for a worker having outdoor activities (Sakumi et al, 2016). A study conducted by the Fukushima Medical University (FMU) with the Iitate factory and other companies located in the evacuated areas showed that the general health of workers could be deteriorated by overtime work and commuting-time, decreased physical activity and sleeping time (Orui et al, 2018).…”
Section: Case Studymentioning
confidence: 99%
“…A number of studies present dosimetry calculations for various contamination scenarios and remediation options (Kamboj et al 2009; Thiessen et al 2009b and c; Furuta and Takahashi 2015), including studies on populations near Fukushima Daiichi (Harada et al 2014; Kinase et al 2015; Naito et al 2016). While these important investigations provide valuable information for stakeholders, studies to quantify the dose incurred by workers performing a remediation effort for roadways and buildings appear to be limited to workers in villages near Fukushima Daiichi (Suto et al 2013; Tsubokura et al 2013; Etherington et al 2014; Sakumi et al 2015). The present study focuses on the common radionuclide 137 Cs because this radionuclide is a dominating, long-term gamma-ray source term for nuclear detonations, some radionuclide dispersal devices, and nuclear reactor accidents (Leikin et al 2003).…”
Section: Introductionmentioning
confidence: 99%